(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the purpose, possibilities, pedagogical conditions and factors of developing the creative competence of future teachers based on the acmeological approach. Based on the acmeological approach, the pedagogical model of developing the creative competence of future teachers and the modern methods of its implementation are highlighted.